2015
DOI: 10.1007/s11356-015-4743-9
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen and phosphorus associating with different size suspended solids in roof and road runoff in Beijing, China

Abstract: Roofs and roads, accounting for a large portion of the urban impervious land surface, have contributed significantly to urban nonpoint pollution. In this study, in Beijing, China, roof and road runoff are sampled to measure the suspended solids (SS), nitrogen (N), and phosphorus (P) contained in particles with different sizes. The SS content in the road runoff (151.59 mg/L) was sevenfold that in the roof runoff (21.13 mg/L, p<0.05). The SS contained more coarse particulates in the roof runoff than in road runo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…It is possible that sediment and organic material (i.e. TSS) transported during the runoff event also transported particulate-P but at a varied time scale influenced by change in flow intensity, suspended particle size, and the speciation of P [25, 56, 57]. Studies show that particulate-P is the dominant form in urban runoff and that accumulation of P in urban regions is mainly a surface issue, whereby particulate-P, associated with the finer fraction (1–25 microns) of sediment, accumulates on impervious surfaces and is then transported into surface waters by rain or irrigation events [5861].…”
Section: Resultsmentioning
confidence: 99%
“…It is possible that sediment and organic material (i.e. TSS) transported during the runoff event also transported particulate-P but at a varied time scale influenced by change in flow intensity, suspended particle size, and the speciation of P [25, 56, 57]. Studies show that particulate-P is the dominant form in urban runoff and that accumulation of P in urban regions is mainly a surface issue, whereby particulate-P, associated with the finer fraction (1–25 microns) of sediment, accumulates on impervious surfaces and is then transported into surface waters by rain or irrigation events [5861].…”
Section: Resultsmentioning
confidence: 99%
“…The TOC content in road dust was also positively correlated with annual daily traffic. Wu, Ren et al (2015) reported 94% of suspended sediment in road runoff being smaller than 50 µm, compared to only 59% smaller than 50 µm in roof runoff in Beijing, China. Sources of nutrients can influence the type of treatment that is effective for its removal.…”
Section: Stormwater Quantitymentioning
confidence: 98%
“…Other than monitoring the natural aquatic set up, physicochemical profiling has been intensively utilized to monitor the polluting properties of treated wastewaters and effluents coming from either point source or non-point source pollution releasers. For instance, urban runoff which carries pollutants into receiving waterways [29], such as dissolved nitrogen, phosphorus associated particles, and suspended solids from roofing materials and roads runoffs known to exceed the standardized surface water quality [30] have been monitored through physical measurement of the mean concentration of these pollutants [31]. Some examples of physicochemical data of wastewaters are shown in Table 2.…”
Section: Physicochemical Characterization In Monitoring Environmental Pollutionmentioning
confidence: 99%